2019
DOI: 10.1097/phm.0000000000001080
|View full text |Cite
|
Sign up to set email alerts
|

The “Minimum Clinically Important Difference” in Frequently Reported Objective Physical Function Tests After a 12-Week Renal Rehabilitation Exercise Intervention in Nondialysis Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) patients are characterized by impaired physical function. The goal of exercise-based interventions is an improvement in functional performance. However, improvements are often determined by 'statistically significant' changes. We investigated the 'minimum clinically important difference' (MCID), 'the smallest change that is important to the patient', for commonly reported physical function tests. Design Non-dialysis CKD patients completed 12-weeks of a combined aerobic (plus resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…We observed a modest, nonsignificant increase in ⩒O 2peak of 0.8 mL/min kg -1 or ~4%. This result is well below the generally accepted minimal clinically important difference of 1.5 mL/min kg -1 [ 25 ] and supports the conclusions of some previous exercise studies in CKD that showed inadequate change [ 26 , 27 ]. Nevertheless, it does contrast with most of the findings from a recent systematic review and meta-analysis that reported a pooled increase of 2.4 (1.0 to 3.8) mL/min kg -1 (~11%) in patients with CKD following exercise [ 17 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed a modest, nonsignificant increase in ⩒O 2peak of 0.8 mL/min kg -1 or ~4%. This result is well below the generally accepted minimal clinically important difference of 1.5 mL/min kg -1 [ 25 ] and supports the conclusions of some previous exercise studies in CKD that showed inadequate change [ 26 , 27 ]. Nevertheless, it does contrast with most of the findings from a recent systematic review and meta-analysis that reported a pooled increase of 2.4 (1.0 to 3.8) mL/min kg -1 (~11%) in patients with CKD following exercise [ 17 ].…”
Section: Discussionsupporting
confidence: 86%
“…Notably, we found that the increase after exercise was identical to that observed during the control period. Previous work by our group has shown that the minimal detectable change in ⩒O 2peak is 0.5 mL/min kg -1 [ 25 ], and as such, the change in ⩒O 2peak observed here is likely due to methodological limitations and the error inherent in this test. Improvements in relative ⩒O 2peak (i.e., adjusted for kg) could also be explained by the concurrent changes in body mass seen throughout the study.…”
Section: Discussionmentioning
confidence: 63%
“…Objectively measured maximal aerobic exercise capacity using standardized testing protocols is strongly associated with survival in health ( 39 ) and CF lung disease ( 6 , 40 , 41 ). Based on ITT analysis, the magnitude of improvement in Wpeak (8.1% predicted [95% CI, 3.6–12.6] at 6 months, and 6.6% predicted [95% CI, 3.0–10.2] at 12 months) and peak (4.5% predicted [95% CI, 1.0–8.0]) at 12 months in the intervention group compared with the control group) may be considered clinically relevant ( 42 ). However, whether improvements in exercise capacity translate into better survival is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of data on the minimum clinically important difference (MCID) of V Ȯ2, particularly in patients with OSA, but values ranging between 1.5 and 2.0 mL$kg -1 $min -1 have been reported in other groups of patients using either anchor-based, distributionbased, or arbitrarily defined methods. 39,40 Others have defined "responders" to interventions based on detectable differences in V Ȯ2 greater than the technical error of measurement, which may range from 1.5 to 1.8 mL$kg -1 $min -1 . 41,42 The subgroup analysis within this review found a relationship between baseline BMI and ΔV Ȯ2 max and V Ȯ2 peak, with higher baseline BMI being associated with smaller changes in V Ȯ2 max and V Ȯ2 peak with CPAP treatment.…”
Section: Discussionmentioning
confidence: 99%